Звезда: роман / Даниэла Стил ; [перевод с английского Е. А. Ивановой] - Стил Даниэла (АСТ, 2000)
Экземпляры: ф.7 (2001) / Инвентарный номер: 42929 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: С 80 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44